Processo de extração de óleo essencial de Achyrocline satureioides (LAM) DC. por arraste a vapor : modelagem, análise do potencial aromático e retificação de compostos - Pires, Vinícius Pereira (2017)
The essential oils are of great economic importance for several sectors of the world industry due to the varied range of properties and for being an alternative to the synthetic substances existing in the market. One way of obtaining these essential oils is through the technique of steam distillation, process widely used due to simplicity and low cost. The goals of this work were to obtain the essential oil of the species Achyrocline satureioides by steam distillation in different operating conditions, heading to model this process mathematically, to obtain the volatile compounds present in the essential oil by solid phase microextraction (SPME) technique, to analyze the oil and the volatile compounds accomplished by chromatographic/olfatomatric methods and to carry out a theoretical study of the separation of the major compounds of the essential oil by the fractional batch distillation technique. The achieved results demonstrated that the mathematical model, based on the one-dimensional mass balance in the fluid and solid phases to represent the extraction of essential oils in a pilot scale steam distillation unit, fitted well to the experimental data. The major compounds obtained by gas chromatography/mass spectrometry (GC/MS) were E-Caryophyllene, α-Pinene, α-Copaene and α-Humulene. In addition, it can be observed by gas chromatography/olfactometry (GC/O) that the major compounds, of higher concentrations, do not present the highest aromatic intensities, except for the α-Pineno compound that presented high concentration and aromatic intensity. The methodology applied to fractional distillation of the A.satureioides oil showed potential in the development of essential oil fractioning processes, since a high purity (99.10%) was obtained in the α-Pinene fraction.